Terapi Kognitif Sebagai Intervensi Keperawatan untuk Mengatasi Ketidakberdayaan pada Pasien Kanker - Elizabeth Risha Murlina Lema; Hasanudin Hasanudin (Journal of Telenursing (JOTING), 2026)
This study aims to determine the application and effectiveness of cognitive therapy in reducing signs and symptoms of helplessness in cancer patients. The method used is a case series study design. The results showed that patients had an average of 25.4 signs of helplessness. After initial intervention, cognitive therapy significantly reduced the number of symptoms further to an average of 8.1, with an average total reduction of 17.3 symptoms per patient. The greatest reduction was seen in the cognitive domain (e.g., reduced doubts and negative thoughts) and affective domains (e.g., reduced anxiety and depressed mood). In conclusion, the application of cognitive therapy as a specialist mental health care intervention was significantly effective in reducing signs and symptoms of helplessness in cancer patients. This intervention successfully improved patients' ability to manage negative thoughts, which had a positive impact on their affective, behavioral, and social conditions. Cognitive therapy empowers patients with adaptive coping skills, helps them rebuild a sense of control, and has the potential to improve quality of life during the challenges of cancer treatment.   Keywords: Cancer, Helplessness, Cognitive Therapy